Educational strategy to modify unhealthy lifestyles in malnutried young adults: Educational strategy to modify unhealthy lifestyles in malnutried young adults - Figueroa, Glenda; Muñoz, Lenin; Villamil, Karen; Rosero, Germania (REDIELUZ, 2021)
In the last decades, the increase in the figures of the prevalence of obese people worldwide is no-torious, related to the increase in chronic diseases such as diabetes mellitus and arterial hypertension. The objective of this research is to design an edu-cational strategy to modify unhealthy lifestyles in young adults with malnutrition. A descriptive, ob-servational, cross-sectional study was carried out in young adults with excess malnutrition, a survey was made to determine knowledge about healthy lifestyles, developing an educational strategy to mo-dify ignorance. Overweight prevailed with 57.7% in the group between 30 to 34 years (32%), the fema-le sex (60.8%) and secondary schooling (46.4%), the civil status free union (55.7% ), self-employment (49.5%), and mestizo ethnicity (67.0%). The knowle-dge of excess weight as a health problem represen-ted 91.8%. The lack of knowledge about healthy ea-ting was 78.4%, 59.8% were aware of food groups, 50.5% of physical exercises, and 58.8% of associa-ted diseases were greater. The preferred educatio-nal strategy was talks for 30 minutes (70.1%), once a week 43.3% and in the morning (87.6%).